People's Republic of China Financial Sector Assessment Program : Basel Core Principles for Effective Banking Supervision - International Monetary Fund; World Bank (World Bank, Washington, DC, 2017)
Regulation and supervision of China's banking system has made impressive progress in the past few years, led by an activist, forward-looking regulator China Banking Regulatory Commission (CBRC), with a clear safety and soundness mandate that has been supported by banks and by the State. Less than fully compliant ratings in certain areas in this assessment generally reflect deficiencies in the legal framework, which can be amended, or that banks have yet to fully implement CBRC guidance. This assessment of the current state of the implementation of the Basel Core Principles for Effective Banking Supervision (BCP) in China has been completed as part of a Financial Sector Assessment Program (FSAP) undertaken jointly by the International Monetary Fund (IMF) and the World Bank between June 7 and June 25, 2010, and reflects the regulatory and supervisory framework in place as of the date of the completion of the assessment.